Accelerating implementation of adolescent digital health prevention programs: analysis of insights from Australian stakeholders - Raeside, Rebecca; Todd, Allyson; Sim, Kyra A.; Kang, Melissa; Mihrshahi, Seema; Gardner, Lauren A.; Champion, Katrina E.; Skinner, John; Laranjo, Liliana; Steinbeck, Katharine; Redfern, Julie; Partridge, Stephanie R. (Frontiers in Public Health, 2024)
Background: Chronic disease risk factors are increasing amongst adolescents, globally. Digital health prevention programs, which provide education and information to reduce chronic disease risk factors need to be equitable and accessible for all. For their success, multiple highly engaged stakeholders should be involved in development and implementation. This study aimed to evaluate stakeholders' support for, and perspectives on potential public health impact of digital health prevention programs for adolescents and potential pathways for future implementation.Methods: Qualitative semi-structured online interviews with stakeholders. Stakeholder mapping identified key individuals, groups and organizations across Australia that may influence the implementation of digital health prevention programs for adolescents. Recorded and transcribed interviews were analyzed within the Reach, Effectiveness, Adoption, Implementation and Maintenance (RE-AIM) Framework, using deductive content analysis.Findings: Nineteen interviews were conducted in 2023 with stakeholders from government, health, non-government organizations, youth services, education, community settings and others. Four overarching themes were identified: (i) existing digital health initiatives are not fit for purpose; (ii) the co-creation of digital health prevention programs is critical for successful implementation; (iii) digital health prevention programs must address equity and the unique challenges raised by technology and; (iv) system level factors must be addressed.Interpretation: Stakeholders broadly supported digital health prevention programs, yet raised unique insights to ensure that future programs create public health impact by improving chronic disease risk factors among adolescents. These insights can be applied in future development of digital health prevention programs for adolescents to strengthen widespread implementation.